In Situ Synthesis of a Magnetic Graphene Platform for the Extraction of Benzimidazoles from Food Samples and Analysis by High-Performance Liquid Chromatography - Qianchun Zhang; Yulan Liu; Xingyi Wang; Huimin Li; Junyu Chen (Journal of Analytical Methods in Chemistry)
A novel method was proposed for the determination of five benzimidazoles (oxfendazole, mebendazole, flubendazole, albendazole, and fenbendazole) using magnetic graphene (G-Fe3O4). G-Fe3O4 was synthesized via in situ chemical coprecipitation. The properties of G-Fe3O4 were characterized by various instrumental methods. G-Fe3O4 exhibited a great adsorption ability and good stability towards analytes. Various experimental parameters that might affect the extraction efficiency such as the amount of G-Fe3O4, extraction solvent, extraction time, and desorption conditions were evaluated. Under the optimized conditions, a method based on G-Fe3O4 magnetic solid-phase extraction coupled with high-performance liquid chromatography was developed. A good linear response was observed in the concentration range of 0.100–100 μg/L for the five benzimidazoles, with correlation coefficients ranging from 0.9966 to 0.9998. The limits of detection (S/N=3) of the method were between 17.2 and 32.3 ng/L. Trace benzimidazoles in chicken, chicken blood, and chicken liver samples were determined and the concentrations of oxfendazole, mebendazole, flubendazole, and fenbendazole in these samples were 13.0–20.2, 1.62–4.64, 1.94–6.42, and 0.292–1.04 ng/g, respectively. The recovery ranged from 83.0% to 115%, and the relative standard deviations were less than 7.9%. The proposed method was sensitive, reliable, and convenient for the analysis of trace benzimidazoles in food samples.